Estimation of Manganese in Ferromanganese Slag - A.V.L.N.S.H. HARIHARAN; K.Y. KARUNA (Chemical and Materials Sciences: Research Findings Vol. 2, 2025)
Leaching of manganese from ferromanganese slag (Garividi, Vizianagram Dt.) was effectively done by using both hydrochloric and perchloric acid solutions. It was noticed that the rate of leaching is more temperature sensitive and dependent on the nature of the acid solution used in these studies. Solvent extraction of manganese [Mn (II)] by tri-n-octylamine (TOA) dissolved in xylene from hydrochloric and perchloric acid media has been carried out. Extractions are nearly quantitative from both acid solutions. The effect of concentrations of acid, metal, and TOA and diluent on the extraction has been studied. Maximum efficiency is obtained with xylene as diluent. Stripping of manganese from the organic phase was quantitatively achieved with 1.0M HNO3. The extracted species was also identified as [Mn X2. (2TOA)], (X=chloride or perchlorate). Attempts made for the estimation of manganese were successful in the presence of other metals and impurities usually associated with ferromanganese slag.